Crisis amidst Abundance: Food Security in Bangladesh - Siddiqui, A.; Hossain, Amzad; Marinova, Dora (Cambridge Scholars Publishing, 2016)
Food security is a major problem for the globe and for many Indian Ocean countries. Bangladesh is one of them and the chapter focuses on this issue relating it to the specific cultural and geo-environmental context of the country. It argues that food insecurity exists in Bangladesh in the form of crisis amidst abundance. In the past, Bangladesh was a nation of food surplus attracting visitors from abroad. Its self-reliant food security earned it the title of ‘paradise of nations’. Since the 1970s however the injurious impacts of multifaceted globalization, including the Green Revolution, resulted in major changes creating food insecurity. The application of chemicals and intensive cultivation of mono-crops have destroyed the water-based distribution system. Furthermore, the health of the country’s numerous waterways has sharply declined due to excessive use for irrigation and many of them are no longer flowing. The post-1970 political crises in Bangladesh have also triggered corruption in food management. All this has made Bangladesh a struggling nation in the Indian Ocean region. The chapter tackles the issues from a remedial point of view. It combines the authors’ field experience and relevant literature to discuss the frontiers of food security. A renewal of Bangladesh’s dying waterways is essential to achieve sustainable food production but this also required meaningful collaboration between the Indian Ocean countries. Reviving traditional sustainability-oriented practices of growing and distributing agricultural produce can prevent the further exacerbation of the current food crisis. Bangladesh’s resilient, simple living and innovative human resources, including the syncretistic mystic tradition of Baul-philosophers, can provide a sustainability platform for the future of the country and the Indian Ocean region.